Perkawinan Beda Agama: Antara Hak Asasi Manusia Dan Aturan Agama Persfektif Hukum Positif - Ningrum, Fara Puspita Aqila; Rodliyah, Nunung; Firmansyah, Ade Arif; Budiyono, Budiyono; Adhan. S., Sepriyadi (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
The polemic regarding interfaith marriage in indonesia reflects the tension between positive law, religious values and the principles of human rights (HAM) the marriage law explains that a marriage is valid if it is carried out in accordance with each religion, making it difficult for interfaith couples to legally marry. If we look at the universal declaration of human rights (DUHAM), it gives everyone the freedom to marry regardless og religion. In indonesia, religious views on interfaith marriage also vary, some religious prohibit it, while others allow it with certain conditions. These diffrences in rule and views cause confusion and legal uncertainty. Therefore, clearer and fairer rules are needed so that everyone’s right to marry can still be respected without ignoring existing religious values.